Appraisement and Analysis of Dynamical Stability of Under-Constrained Cable-Driven Lower-Limb Rehabilitation Training Robot. Issue 6 (10th June 2021) - Wang, Yan-Lin; Wang, Ke-Yi; Wang, Wan-Li; Han, Zhuang; Zhang, Zi-Xing
SUMMARY: The dynamical stability of the cable-driven lower-limb rehabilitation training robot (CLLRTR) is a crucial question. Based on the established dynamics model of CLLRTR, the solution to the wrench closure of the under-constrained system is presented. Secondly, the stability index of CLLRTR is proposed by the Krasovski method. Finally, in order to analyze the stability distribution of CLLRTR in the workspace, the stability evaluation index in the workspace is calculated using the eigenvalue decomposition method. The stability distribution laws of CLLRTR are further verified by the experimental study. The results provide references for studying trajectory planning and anti-pendulum control of CLLRTR.